Molecular Identification of Cervical Microbes in HIV-Negative and HIV-Positive Women in an African Setting Using a Customized Bacterial Vaginosis Microbial DNA Quantitative PCR (qPCR) Array - Taku, Ongeziwe; Onywera, Harris; Mbulawa, Zizipho Z. A.; Businge, Charles B.; Meiring, Tracy L.; Williamson, Anna-Lise (Microbiology Spectrum, 2022)
Bacterial vaginosis (BV) is a common polymicrobial vaginal disorder that is associated with sexually transmitted infections (STIs), including HIV. Several studies have utilized broad-range 16S rRNA gene PCR assays with sequence analysis to characterize cervicovaginal bacterial communities of women with healthy and diseased conditions. With the high burden of BV and STIs among African women, there is a need for targeted PCR assays that can rapidly determine the true epidemiological profile of key cervical microbes, including BV-associated bacteria, and a need to explore the utility of such assays for microbiological diagnosis of BV. Here, we used a taxon-directed 16S rRNA gene quantitative PCR (qPCR) assay to examine the prevalences and determinants of specific cervical microbes among African women with and without HIV infection. Cervical samples were collected using a cytobrush from 162 women (aged $30 years) attending a community-based clinic in Eastern Cape, South Africa. The samples were screened for specific microbes (i.e., STIs, emerging sexually transmitted pathogens [pathobionts], and BV-associated bacteria) using a customized bacterial vaginosis microbial DNA qPCR array. Statistical analyses were performed using GraphPad Prism v6.01. Chi-square/Fisher’s exact tests were used to evaluate the determinants associated with specific cervical microbes. Only 145 women had any detectable microbes and were included in the analysis. Lactobacillus iners (62.8%) and specific BV-associated bacteria, namely, Gardnerella vaginalis (58.6%), Atopobium vaginae (40.7%), and the pathobiont Ureaplasma parvum (37.9%), were the most prevalent microbes. Hierarchical clustering analysis revealed that 42.8% of the women (62/145) had a diverse array of heterogeneously distributed bacteria typically linked to BV. Women with detectable Lactobacillus species, specifically Lactobacillus crispatus and Lactobacillus jensenii, and to a lesser extent L. iners, had very low prevalence of BV-associated bacteria. Although the cumulative burden of STIs/pathobionts was 62.8%, Chlamydia trachomatis (3.4%), Neisseria gonorrhoeae (4.8%), and Trichomonas vaginalis (4.8%) were detected at low rates. HIV infection was associated with the presence of STIs/pathobionts (P = 0.022) and L. iners (P = 0.003). Prevalent STIs/pathobionts were associated with having multiple partners in the past 12 months (n $ 2, P = 0.015), high number of lifetime sexual partners (n $ 3, P = 0.007), vaginal sex in the past month (P = 0.010), and decreasing age of women (P = 0.005). C. trachomatis was associated with increasing age among HIV-positive women (P = 0.016). The pathobiont Ureaplasma urealyticum was inversely associated with age of women in the whole cohort (P = 0.018). The overall prevalence of STIs/pathobionts was high and was associated with HIV infection and sexual behavior. Our study helps us to understand the epidemiological trend of STIs and pathobionts and highlights the need to understand the impact of sexual networks on STI and pathobiont transmission and prevention among women in an African setting.
Keywords: HIV; Cervical microbes; Bacterial vaginosis (BV); Sexually transmitted infection (STI); Emerging sexually transmitted pathogen (pathobiont); African women; Bacterial vaginosis microbial DNA qPCR array